2008
DOI: 10.1139/h07-189
|View full text |Cite
|
Sign up to set email alerts
|

The time course of denervation-induced changes is similar in soleus muscles of adult and old rats

Abstract: Muscle denervation is accompanied by atrophy and a decline in oxidative capacity. We investigated whether the time course of adaptations following denervation of the soleus muscle differs in adult (5 months old) and older adult (25 months old) rats. We denervated the soleus muscle of the left leg, while the right leg served as an internal control. Two weeks after denervation, muscle mass was decreased both in adult and old animals to, respectively, 57% and 54% (p < 0.001) and capillary to fibre ratio (C:F) dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 33 publications
9
35
0
Order By: Relevance
“…These observations are also robust to variations in the adjustable parameters of the transport model (Al-Shammari et al, 2012). Therefore, in the absence of extremes that are only associated with pathologies, our modelling predicts that VP provide a computationally simple and accurate approximation of functional capillary supply for muscle tissue cross sections of heterogeneous fibre types, which in turn theoretically validates the conclusions of modelling studies taking Voronoi polygons as a basis for morphometric analyses of maximal capillary supply in skeletal muscle tissues (Degens et al, 1992(Degens et al, , 2002(Degens et al, , 2006(Degens et al, , 2008Egginton et al, 2001;Wüst et al, 2009a;Ahmed et al, 1997).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These observations are also robust to variations in the adjustable parameters of the transport model (Al-Shammari et al, 2012). Therefore, in the absence of extremes that are only associated with pathologies, our modelling predicts that VP provide a computationally simple and accurate approximation of functional capillary supply for muscle tissue cross sections of heterogeneous fibre types, which in turn theoretically validates the conclusions of modelling studies taking Voronoi polygons as a basis for morphometric analyses of maximal capillary supply in skeletal muscle tissues (Degens et al, 1992(Degens et al, , 2002(Degens et al, , 2006(Degens et al, , 2008Egginton et al, 2001;Wüst et al, 2009a;Ahmed et al, 1997).…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, Voronoi polygons (Fig. 1B) generate a space-filling alternative (Egginton & Ross, 1989 thereby allowing the exploration of the local influences associated with microvascular remodelling, as well as any mismatch between angiogenesis and local O 2 demand (Degens et al, 1992(Degens et al, , 2002(Degens et al, , 2006(Degens et al, , 2008Egginton et al, 2001;Wüst et al, 2009a). This gives Voronoi polygons an advantage in assessing the efficacy of applications to pathological scenarios, such as ischaemia, where potential therapeutic interventions include strength training (Deveci & Egginton, 2002;Suzuki et al, 2000), endurance exercise (Ahmed et al, 1997;Scott et al, 2009), electrical stimulation (Ebina et al, 2002), and alterations in muscle temperature (Egginton et al, 2001;Egginton, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…the gastrocnemius [Chernukh and Alekseeva, 1975;Tyml et al, 1999] and soleus muscles [Čebašek et al, 2006;Degens et al, 2008], show regression of capillaries already in the early denervation period. Tyml et al [1999] speculated that such a specific postponed decrease in EDL capillaries to early denervation could be a consequence of the specific high susceptibility of EDL muscles to sympathectomy, because they have observed an increased blood flow after tetrodotoxin denervation (that could induce angiogenesis or prevent rarefaction of capillaries) only in the EDL but not in gastrocnemius muscles.…”
Section: Muscle Fibre Morphometry and Capillary Characteristicsmentioning
confidence: 99%
“…Yet, we did not observe a more homogeneous distribution of capillaries after exposure to hypoxia, not even in the glycolytic region that became more oxidative. Also, during hypertrophy (16) and atrophy (15), the heterogeneity of capillary spacing remains unaltered, and it has been suggested that the absence of changes might be related to physical constraints, determined by the morphology of the muscle fibers, of placing new capillaries (16).…”
Section: Overall Adaptations To Chronic Hypoxiamentioning
confidence: 99%